Efforts of Collage Activities Using Waste Recycling on Primary School Students' Creativity - Elfara Putri Fauziah; Wasis Wijayanto (Jurnal Prajaiswara, 2024)
Abstract—Collage or collage art is a type of fine art created by attaching pieces, fragments or any materials originating from waste or unused items and attaching them to the image area to create a result. This research has a problem formulation, namely to determine the level of student creativity through collage activities using recycled waste in class 1 of SD NEGERI 3 SIDIGEDE JEPARA. The aim of this research is to describe the influence of collage activities through the use of recycled waste on student creativity in class 1 of SD NEGERI 3 SIDIGEDE JEPARA. The research was conducted in class 1 of SD N 3 SIDIGEDE, totaling 15 students. The research method uses a descriptive qualitative approach, with research instruments in the form of observation, interviews and documentation. The results of the research are that the influence of collage activities using recycled waste on elementary school students' creativity is quite well developed and very influential. Students are very enthusiastic and creative, although there are still some students who are still accompanied, given direction and helped by the teacher.